The Journal landfill - Romero, Leonardo (2012)
The interest in publishing the results of our investigations is inherent to research, we investigate to find the truth and communicate what we find. However, like a living entity is molded by the circumstances or environment in which it lives, scientific research and publications are evolving as a consequence of social, economic and cultural change.